Statistical Approach for Optimization of Physiochemical Requirements on Alkaline Protease Production from Bacillus licheniformis NCIM 2042. (23rd October 2011) - Bhunia, Biswanath; Dey, Apurba
Abstract : The optimization of physiochemical parameters for alkaline protease production using Bacillus licheniformis NCIM 2042 were carried out by Plackett-Burman design and response surface methodology (RSM). The model was validated experimentally and the maximum protease production was found 315.28 U using optimum culture conditions. The protease was purified using ammonium sulphate (60%) precipitation technique. The HPLC analysis of dialyzed sample showed that the retention time is 1.84 min with 73.5% purity. This enzyme retained more than 92% of its initial activity after preincubation for 30 min at37 ∘ C in the presence of 25% v/v DMSO, methanol, ethanol, ACN, 2-propanol, benzene, toluene, and hexane. In addition, partially purified enzyme showed remarkable stability for 60 min at room temperature, in the presence of anionic detergent (Tween-80 and Triton X-100), surfactant (SDS), bleaching agent (sodium perborate and hydrogen peroxide), and anti-redeposition agents (Na2 CMC, Na2 CO3 ). Purified enzyme containing 10% w/v PEG 4000 showed better thermal, surfactant, and local detergent stability.